Public relations strategy in rebuilding Airline Company reputation following aircraft crash - Mudiardjo, Rapin; Ariantoro, Muhammad Firdaus; Supriyadi, Iwan; Aras, Muhamad; Hidayat, Z. (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The issue discussed in this study is rebuilding Lion Air's reputation tarnished by aircraft accidents. This study aims to identify public relations strategies pursued by case study of Lion Air, Indonesia, to rebuild its reputation following air accidents it has been involved. The research method employed in this study is the qualitative method using single case studies on Lion Air Company. Data is collected through observation, interviews, and a review of news articles in the media. The output of the research takes the form of corporate strategies that are aimed at rebuilding the company's reputation using stakeholder approaches, including (1) alignment of internal perceptions within the organization; (2) "communication holding,"; (3) centralization of information issuance; (4) appointment of partners as "communicators"; (5) use of humanitarian approaches. The conclusion drawn from the research is that public relations strategies through a stakeholder approach would provide a basis for Lion Air's management to exercise control over information that brings positive value. The result also shapes stakeholders' perceptions to align with the company's expectation in restoring its reputation.